A morphological analysis of research literature on Lean Six Sigma for services. Issue 1 (2nd January 2018) - Sunder M., Vijaya; Ganesh, L.S.; Marathe, Rahul R.
Abstract : Purpose: The purpose of this paper is to review the existing literature on Lean Six Sigma (LSS) for services, construct a morphological analysis (MA) framework and identify research gaps to point to future research possibilities and priorities. Design/methodology/approach: The MA framework is based on literature review of 175 papers published from 2003 to 2015, across 67 journals recognised by Scopus or ABS Academic Journal Quality Guide 2015. A three-phased methodology is used by the authors, with Phase1 featuring a five-stage systematic review protocol to identify relevant journal papers for review; Phase2 presenting a framework for classifying the reviewed papers in terms of their fundamental, methodological, chronological and sector-wise orientations; and Phase3 constructing an MA framework on the classified papers and identifying the research gaps. Findings: The MA framework constructed based on six dimensions, namely, organizational context of applications, desired outcomes, implementation systems, LSS tools and techniques, integration with other management philosophies and evaluation methods, involving 40 focused themes, has revealed 355 distinct research gaps as opportunities for future research. Practical implications: This paper confirms the existence of substantial scope and points to specific topics for further research in the area of LSS for services. The findings demonstrate the gaps in academic research on the subject. In addition, the study also helps organisational leaders and practitioners to look at LSS from a holistic perspective in the services context. Originality/value: The MA framework of the existing literature on LSS for services presents a unique, systematic effort to identify research opportunities. In addition, a five-stage systematic review protocol is proposed in this paper. This could be valuable to researchers and practitioners in enabling them to systematically review the literature on research subjects of interest to them.